Reorganising the Banks: Focus on the Liabilities, Not the Assets. - Bulow, J; Klemperer, P (Centre for Economic Policy Research, 2009)
Fixing the banks is an absolute priority in G7 nations. Doing this by buying toxic assets is costly, inefficient, and risky. Governments should focus on which liabilities, rather than which assets, they need to support. This column proposes creating “bridge” banks as a way of re-establishing a healthy banking system.